2014
DOI: 10.1007/s11105-014-0803-4
|View full text |Cite
|
Sign up to set email alerts
|

Divergent and Overlapping Function of Five 4-Coumarate/Coenzyme A Ligases from Populus tomentosa

Abstract: 4-Coumarate/coenzyme A ligases (4CLs) play key roles in the biosynthesis of plant secondary compounds and act at the divergence point from general phenylpropanoid metabolism to several major branch pathways, such as lignins and flavonoids. In this study, five 4CL genes in Populus tomentosa were cloned and characterized. Quantitative polymerase chain reaction (qPCR) and promoter-β-glucuronidase analysis showed that the expression of Pto4CLs is significantly divergent and certainly overlapping. The five Pto4CL r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The 4CL gene family has been characterized in several plants, including Arabidopsis thaliana, Populus trichocarpa, Oryza sativa and Glycine max [11,[23][24][25]. Genes of this family have been reported to function not only in plant growth and development [16,22,26], but also in response to biotic and abiotic stresses [7,27]. However, no comprehensive analysis of the 4CL genes has been documented in G. hirsutum.…”
Section: Discussionmentioning
confidence: 99%
“…The 4CL gene family has been characterized in several plants, including Arabidopsis thaliana, Populus trichocarpa, Oryza sativa and Glycine max [11,[23][24][25]. Genes of this family have been reported to function not only in plant growth and development [16,22,26], but also in response to biotic and abiotic stresses [7,27]. However, no comprehensive analysis of the 4CL genes has been documented in G. hirsutum.…”
Section: Discussionmentioning
confidence: 99%
“…The 4CL gene family has been characterized in several plants, including Arabidopsis thaliana, Populus trichocarpa, Oryza sativa and Glycine max [12,[29][30][31]. Genes of this family have been reported to function not only in plant growth and development [13,28,[32][33], but also in response to biotic and abiotic stresses [7,34,35]. However, no comprehensive analysis of the 4CL genes has been documented in G. hirsutum.…”
Section: Discussionmentioning
confidence: 99%
“…Gh4CL7 belongs to class I whose genes have been shown to regulate lignin synthesis [21,28]. We investigated whether or not Gh4CL7 is also involved in lignin biosynthesis by comparing the lignin contents of the Gh4CL7-OE Arabidopsis lines and TRV:Gh4CL7 cotton plants with that of their corresponding control plants.…”
Section: Gh4cl7 Plays An Important Role In Lignin Biosynthesismentioning
confidence: 99%
“…Furthermore, Li et al (2015) showed that the At4CL1 and At4CL3 genes of Arabidopsis were both involved in the biosynthesis of sinapoylmalate. In Populus tomentosa, its five Pto4CL genes also displayed an overlapping function in lignin biosynthesis (Rao et al 2015). The existence of multiple 4CL genes could be viewed as a strategy to safe-guide the integrity of important metabolic pathways that serve for plant growth and development like lignification where a loss-of-function mutation in one copy of the gene could be rectified by another copy.…”
Section: Gtacmentioning
confidence: 99%
“…The type I 4CL genes are responsible for lignification while the type II 4CL genes are involved in the biosynthesis of flavonoid compounds. Suppression of the type I 4CL genes led to a significant reduction in lignin content in different plants (Gui et al 2011;Xu et al 2011a), while overexpression increased the lignin content (Rao et al 2015). On the other hand, suppression of the type II 4CL gene only led to a reduction in eugenol content in Ocimum sanctum, without affecting the lignin content (Rastogi et al 2013).…”
Section: Introductionmentioning
confidence: 99%